Aesthetic restoration of anterior teeth with monolithic self-glazed zirconia crowns via a completely digital workflow: a clinical case report. (17th August 2020) - Wu, Zhe; Shi, Andi; Liang, Qian; Liu, Tiantao; Huang, Jiangyong; Shen, Zhijian
ABSTRACT: This case represents aesthetic restoration by full-contour monolithic zirconia crowns without porcelain veneer via a completely digital workflow. Virtual prostheses were designed following intraoral scanning and digital smile design (DSD) process. Polymethyl methacrylate (PMMA)-based provisional restorations were used and adjusted as guide for aesthetic and occlusal evaluation. Definite self-glazed zirconia crowns were delivered by superimposing the abutment teeth and modified temporary crowns in situ . Such novel zirconia crowns were formed by net-shape manufacturing process following biogeneric copying of the provisional crowns. The restorations represented functionally tailored hierarchical structures exhibiting superior smoothness on the surface without conventional manual work of grinding, polishing and veneering. The application of full-contour monolithic zirconia restorations in the anterior region via a completely digital workflow indicates a reliable treatment option.